Additive manufacturing of novel aluminium matrix composites with enhanced strength and processability via boron nitride functionalization - Giuseppe Del Guercio; Federico Bosio; Chinmay Phutela; Stuart Robertson; Nesma T. Aboulkhair (Additive Manufacturing Letters)
The present work systematically investigates the effects of BN nanopowder functionalization on the processability, microstructure and tensile response of the custom Powder Bed Fusion Laser Beam (PBF-LB) Al alloy ‘AMALLOY3D’. The results show that a minor addition of BN (0.3 % by weight) not only produces near fully dense parts (99.91 %), but is also paired with improved flowability, enhancing the overall processability. Electron backscatter diffraction (EBSD) analysis revealed the transformation to a fully equiaxed grain structure in the BN-functionalized material, resulting in a 40 % increase in yield strength. Energy dispersive spectroscopy using a scanning transmission electron microscope (STEM-EDS) was employed to reveal the intricate secondary phases’ arrangements. These observations coupled with the help of the CALPHAD approach led to the reconstruction of the solidification history of AMALLOY3D and the BN-functionalized material. The present study unravels the complex dynamics leading to the columnar-to-equiaxed transition in BN-reinforced AMCs, proving that such unique microstructures and exceptional tensile properties can be achieved without compromising PBF-LB processability.